Universal screening for gestational diabetes mellitus with diabetes in pregnancy study group India criteria and maternal and fetal outcome in gestational diabetes mellitus patients - Gupta, Alisha; Kaur, Amrit Pal; Kaur, Sukhraj; Sharma, Sukriti (International Journal of Research in Medical Sciences, 2024)
Background: The aim of the study was to estimate the incidence of gestational diabetes mellitus (GDM) among antenatal patients and to evaluate the maternal and neonatal complications in GDM cases and compare it with non GDM controls. Methods: This prospective study was conducted at Bebe Nanki maternal and child care centre, Amritsar in the department of obstetrics and gynecology from September 2022 to August 2023. A total of 2600 antenatal patients were screened for GDM using DIPSI (diabetes in pregnancy study group India) criteria. Maternal and fetal outcomes were compared in 200 GDM cases and 200 non GDM controls. Results: Incidence of GDM was found to be 8.69% (226/2600). The mean age of GDM cases v/s controls was 29±5.53 years v/s 26.75±4.55 years respectively. Mean BMI of GDM cases v/s controls was ≥24 kg/m2 v/s 18.5-23.9 kg/m2. Majority of GDM cases 117 (58.5) and controls 140(70%) delivered at term via LSCS (53% cases v/s 49.5% controls delivered via LSCS). Antenatal complications like HDP (17.5% v/s 8%), preterm labour (40.5% v/s 29.5%) and polyhydroamnios (19.5% v/s 1.5%) were more common among GDM cases v/s controls. Surgical site infections (11% v/s 2.5%) and UTI (24% v/s 6%) incidence was higher in GDM cases compared to controls. Neonatal complications like NICU admission (21% v/s 7.5%), sepsis (12% v/s 5.5%) and hypoglycaemia (37.5% v/s 1%) were higher in infants of GDM mothers. Conclusions: Early detection and timely management of GDM cases can improve foetomaternal outcome.